Natural Complexes of Alkaline Earth Metals with Picolinic Acid-N-Oxide and Quinaldinic Acid-N-Oxide - Prakash, D.; Shafayat, M.; Prasad, N.K.; Gupta, O.P. (Asian Journal of Chemistry, 2010)
Complexes of alkaline earth metals belonging to ML2 · nH2O type, where M = Mg, Ca, Sr and Ba, HL = picolinic acid-N-oxide and quinaldinic acid-N-oxide and n = 0 or 2 have been synthesised and characterised on the basis of elemental analysis, conductivity measurements and IR spectral studies.